A organização do ensino de matemática no contexto de inclusão - Lucion, Paula (2015)
This work is part of a project developed within the line of research ―Formation, Knowledge, and Professional Development‖ of the graduate program in Education at Federal University of Santa Maria (UFSM). It is based on studies related to the formation of teachers who teach Math in an inclusion context, aiming at contextualizing Special Education in the Brazilian scenario. To do so, it involved mainly the theoretical assumptions of historical-cultural theory and teaching guiding activity (TGA). As research question this study aims to answer: what elements show to be relevant to the organization of teaching towards the appropriation of the concept of number in an inclusion context? To answer this question, this work investigated the teaching organization towards the appropriation of the concept of number within the inclusion context. To fulfill this objective, the movement of teaching organization directed to two included second graders, who had difficulties in acquiring such concept, was focused. Investigation actions were dynamised in a resource room of a public school situated in Pinhal Grande/RS, where the special educator organized and proposed the specialized teaching activities. In this sense, a didactic unity composed by two teaching activities based on TGA was proposed according to different leaning triggering situations. Data were collected by means of an investigative form, a field diary, audio and video recording, and photographic registers. As far as the analysis of episodes is concerned, it was structured in three moments: 1) the teacher-researcher s organization; 2) ―Camila, the girl who colors drawings‖ a proposal involving one-to-one correspondence; and 3) ―A fun summer afternoon‖ the grouping of activities being focused. In studies of event proceedings, we found indicators of a gradual increase in the number of publications related to the process of teaching and learning Math in the inclusion context, yet the lack of studies on teachers formation in this context is evident. According to data, it is fundamental, in the organization of Math teaching in the inclusion context, that teachers: know the students difficulties and potentialities; seize the logical-historical movement of the concept they are going to work with; engage in actions that allow them the sharing of actions with their peers; be oriented by a solid theoretical-methodological framework. For learning Math in this context, one needs collaboration among peers, mediation from teachers acting in the zone of proximal development by understanding that all students present developing capabilities, the ludic aspect of developed actions, and adaptations due to specific traits presented by students. Evidence shows that TGA, through their theoretical-methodological assumptions, can be transformed into a general way of teaching-organizing action to special education teachers acting in resource rooms.